Application of the vignette technique in a qualitative paradigm - Hazita Azman,; Mahanita Mahadhir, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Vignettes are short depictions of typical scenarios intended to elicit responses that will reveal values, perceptions, impressions, and accepted social norms. This article describes how vignettes were developed and used in a qualitative linguistics anthropology study to elicit those responses as experienced by mixed-heritage individuals in attaining heritage legitimacy despite their inability to speak their heritage languages. The vignettes were administered during in-depth, semi-structured interviews. Eight participants were asked to reflect and respond to prompts which revolved around typical experiences where speakers were limited by their lack of heritage language proficiency. Based on the vignettes, the participants described how the speakers would linguistically strategize to compensate their limited abilities in using the heritage languages. At the same time, the cultural means through which speakers gain legitimacy within their own heritage groups were also identified. Essentially the use of the vignettes facilitated in generating data that would have otherwise been challenging to elicit given the culturally sensitive as well as highly private nature of the phenomena under investigation. The application of vignettes provided a less intrusive and non-threatening way of obtaining perceptions, opinions, beliefs and attitudes based on responses or comments to stories depicting lived experiences of the participants that the researcher is otherwise not privy to as an observer. However, application of this data elicitation technique can prove challenging for the researcher. A critical analysis of the development, implementation and validity of vignettes as a research tool is extrapolated here within the setting of a heritage legitimacy study as an exemplar.